2006
DOI: 10.4049/jimmunol.177.3.1609
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Commitment of Proteolytic Activity of a Purified Recombinant Major House Dust Mite Allergen Der p1 to Sensitization toward IgE and IgG Responses

Abstract: The major proteolytic allergen derived from the house dust mite Dermatophagoides pteronyssinus, Der p1, is one of the most clinically relevant allergens worldwide. In the present study, we evaluate the contribution of the proteolytic activity and structure of a highly purified rDer p 1 to immune responses. Mice were i.p. immunized with three forms of rDer p 1 adsorbed to Alum: one enzymatically active, one treated with an irreversible cysteine protease-specific inhibitor, E-64, and one heat denatured. Immuniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
83
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 73 publications
1
83
0
Order By: Relevance
“…The mature forms were then purified by anion exchange column and sizeexclusion column chromatography. Papain, rDer f 1, and rDer p 1 were treated with an irreversible inhibitor specific to cysteine proteases, E64 (Peptide Institute, Osaka, Japan), as described previously (10), with minor modifications. After the treatment, free E64 was removed by dialysis.…”
Section: Agsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mature forms were then purified by anion exchange column and sizeexclusion column chromatography. Papain, rDer f 1, and rDer p 1 were treated with an irreversible inhibitor specific to cysteine proteases, E64 (Peptide Institute, Osaka, Japan), as described previously (10), with minor modifications. After the treatment, free E64 was removed by dialysis.…”
Section: Agsmentioning
confidence: 99%
“…Protease activity of house dust mite (HDM) major group 1 allergens (Der f 1 and Der p 1), two of the most important allergens common worldwide, has been shown to cause barrier dysfunction, to induce the production of proinflammatory cytokines in epithelial cells and keratinocytes, to cleave various molecules, to modulate functions of various cell types, and to induce Th2 responses (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Papain, a papaya fruit-derived occupational protease allergen, stimulates epithelial cells (12,13) and mouse basophils in vitro (14,15) and induces Th2 responses (14)(15)(16)(17) and IL-33-dependent innate responses of lung eosinophilia in mice (18).…”
mentioning
confidence: 99%
“…At a high concentration of papain (100 g/ml), its cysteine protease activity stimulated murine bone marrow-derived basophils in vitro to produce Th2-inducing cytokines including IL-4 but not release histamine. Cysteine protease activity of our preparations of rDer p 1 and rDer f 1 also crucially commits to the sensitization process in mice (37). Although Phillips et al (60) reported that Der p 1 stimulated purified human basophils to release IL-4, whether its cysteine protease activity is responsible for the basophil activation is unknown because their Der p 1 preparation also contained serine proteases other than Der p 1 (28,61).…”
Section: Discussionmentioning
confidence: 98%
“…Der f 1-specific Abs were detected on plates coated with 5 g/ml rDer f 1 and blocked with ImmunoBlock (DS Pharma Biochemicals), and developed with HRP-conjugated Abs specific to the murine IgE and IgG subclasses as described previously (37,54,55) with some modifications as follows. Sera and detection Abs were diluted with solutions 1 and 2 of CanGetSignal (TOYOBO), respectively.…”
Section: Elisa For Murine Serum Absmentioning
confidence: 99%
See 1 more Smart Citation